The Future of Literary Archives : Diasporic and Dispersed Collections at Risk - Livingstone, Ann, 1951-; Sutton, David C. (Book collections on Project MUSE., 2018)
Literary archives differ from most other types of archival papers in that their locations are more diverse and difficult to predict. The essays collected in this book derive from the recent work of the Diasporic Literary Archives Network, whose focus on diaspora provides a philosophical framework which gives a highly original set of points of reference for the study of literary archives, including concepts such as the natural home, the appropriate location, exile, dissidence, fugitive existence, cultural hegemony, patrimony, heritage, and economic migration.